2012
DOI: 10.1093/jscr/2012.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis: An unusual complication following endoscopic component separation hernia repair

Abstract: Separation of components technique for incisional hernia repair is increasingly utilized as a strategy for hernia repair in both the obese and those with loss of abdominal domain. Endoscopic component separation technique [ECST] is increasingly performed to minimize wound complications associated with the open procedure. We present a case of a patient who developed acute renal failure related to rhabdomyolysis following ECST. A 62-year-old morbidly obese female with BMI of 46 underwent ECST hernia repair for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In other studies, we found that the BMI of those who were selected for the conventional method was higher than in those selected for the endoscopic method, although there was no statistically significant difference, as in our study. In the literature review, the highest BMI among patients who underwent endoscopic CST for GVIH was 46 kg/m², as reported by Todd et al [29]. As a result, we think that obesity is not a relative contraindication in terms of endoscopic or conventional CST.…”
Section: Discussionsupporting
confidence: 56%
“…In other studies, we found that the BMI of those who were selected for the conventional method was higher than in those selected for the endoscopic method, although there was no statistically significant difference, as in our study. In the literature review, the highest BMI among patients who underwent endoscopic CST for GVIH was 46 kg/m², as reported by Todd et al [29]. As a result, we think that obesity is not a relative contraindication in terms of endoscopic or conventional CST.…”
Section: Discussionsupporting
confidence: 56%